Analysis of Medical Procedures Coding Based on ICD-9 CM - Nisa Azhari; Yastori Yastori; Ressa Oashttamadea; Annisa Wahyuni (Iris Journal of Health Information Management, 2022)
The use of the ICD-9 CM in coding medical actions will make it easier for us to classify patient action codes and facilitate reporting and facilitate BPJS claims in the JKN era which are useful as supporting administration, management and health research. This research was conducted at the Regional General Hospital on February 2022. This study aims to determine the highest medical treatment based on ICD-9 CM. This study uses a retrospective descriptive method with a quantitative approach. The research design used in this study was a descriptive cross-sectional study. The population used by all patient medical record files on March 2022 was 568 medical record files. From the results of this study, it is known that there are 3 highest medical actions, namely Tonsilectomy action of 14 patients with code 28.22, Appendectomy action of 12 patients with code 47.09, Mastectomy action of 9 patients with code 85.41.